Resisted sled training for young athletes: when to push and pull - Cahill, M. J.; Cronin, J. B.; Oliver, J. L.; Clark, K. P.; Lloyd, R. S.; Cross, M. R. (Strength and Conditioning Journal, 2020)
There is a renewed interest is resisted sled training (RST); however, little uniformity exists regarding the integration of best practices in RST for young athletes. This article reviews the prescription of load, methods of RST, and the integration of sprint-specific periodized training blocks during the preparatory phase to elicit the greatest gains within different phases of sprint performance such as early acceleration, late acceleration, and the transition to maximum velocity. A targeted, long-term approach to RST may enable more effective development of speed in young athletes.